CASE REPORT OF NON-INSULIN-DEPENDENT HYPOGLYCAEMIA IN RECURRENT SOLITARY FIBROUS TUMOUR OF THE LUNG - Abas, Syarifah Syahirah Syed; Naidu, Tharani; Rajakumar, Radhamani; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Non-islet cell tumour hypoglycaemia (NICTH) is a rare paraneoplastic syndrome that secretes insulin growth factor 2 (IGF2), which results in stimulation of the insulin receptor and subsequently induces hypoglycaemia. Most commonly, IGF2–linked hypoglycaemia has been observed in patients with solid tumours that are either of mesenchymal or epithelial origin, such as hepatocellular carcinomas, adrenocortical tumours, fibrosarcomas and mesotheliomas. CASE A 69-year-old male with underlying hypertension and history of excision of a left solitary fibrous tumour of the left lung 7 years ago presented with recurrent left lung exudative pleural effusion. Chest radiography and CT imaging revealed a left lung mass. Ultrasound-guided biopsy was performed and the histopathology demonstrated recurrence of the solitary fibrous tumour. Debulking surgery was planned; however, while waiting for the surgery, he presented with impaired consciousness and serum glucose on admission was 1.4 mmol/L. He had no prior history of hypoglycaemia. He developed recurrent hypoglycaemia despite continuous dextrose infusion and dietary intervention. At the time of hypoglycaemia, the levels of insulin and C-peptide were suppressed, consistent with non-insulinmediated hypoglycaemia. Additionally, IGF1 levels were below the normal range and his renal, liver and adrenal function were normal. He was started on oral prednisolone and subsequently underwent median sternotomy and tumour debulking surgery. Histopathogical examination confirmed recurrent left lung solitary fibrous tumour. Hypoglycaemia resolved after tumour resection and prednisolone and dextrose infusion were discontinued. After 1 year of follow up, the patient remained well without any further reported hypoglycaemic episodes. CONCLUSION Solitary fibrous tumour is a rare tumour that induces NICTH due to overproduction of IGF2. It is interesting that a few cases reported episodes of hypoglycaemia on recurrence of the tumour, rather than at the initial presentation.